LEGAL ACTION AGAINST WITHDRAWALWAKAF PROPERTY(Decision Study No. 22/Pdt.G/2017/MS-Aceh) - Jiko (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
Withdrawal of Waqf Assets based on Decision No. 22/Pdt.G/2017/MS-Aceh because the objects which are waqf assets belonging to the Bireueen Islamic Education Society have been misused by the Bireueen Ministry of Religious Affairs in a dysfunctional manner, namely the waqf objects are recorded as Public Property. In order for the irregularity of the waqf assets to be in accordance with the waqf pledge made, the owner of the waqf rights takes over the waqf assets. The validity of Nazir as the owner of the waqf rights in the event of misappropriation of waqf assets based on Resolution no. 22/Pdt.G/2017/MS-Aceh is reviewed from the provisions of Article 42 of Law Number 41 of 2004 concerning Waqf which explains: